Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian serta Dampaknya terhadap Pembelian Ulang (Studi Kasus Konsumen Sepatu Ventella di Surakarta) - Arkana, Putut Tio; Isa, Muzakar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research employs a quantitative and descriptive approach to comprehend the factors shaping the repeat purchase patterns of Ventela shoes in Surakarta. The study includes all Surakarta residents who have previously engaged in Ventela product purchases, with a carefully chosen sample of 100 respondents through purposive sampling techniques. Data collection involves the administration of Likert-scale questionnaires, while analysis is executed utilizing SMARTPLS 3.0 software, applying a Structural Equation Model (SEM) framework via Partial Least Squares (PLS). The findings reveal a nuanced perspective: while product quality exerts a positive influence on repeat purchases, its statistical significance is deemed insignificant. Conversely, the impact of price on repeat purchases is both positive and statistically significant. Moreover, both product quality and price wield significant sway over purchase decisions, thereby fostering a culture of repeated buying behavior. These findings not only offer profound insights into the nuanced determinants driving repeat purchasing decisions for Ventela shoes in Surakarta but also furnish strategic implications for product marketing endeavors while paving the way for further exploration in the realm of consumer behavior and purchase decision dynamics. The research aims to enhance understanding of consumer repurchasing patterns for Ventela shoes in Surakarta, enabling companies to optimize their marketing strategies and improve customer satisfaction and loyalty.